Admitting Service Affects Cost and Length of Stay of Hip Fracture Patients - Lott, Ariana (Geriatr Orthop Surg Rehabil, 2018)
INTRODUCTION: The purpose of this study was to analyze the effect of the admitting service on cost of care for hip fracture patients by comparing the cost difference between patients admitted to the medicine service versus those admitted to a surgical service. METHODS: A 2-year cohort of patients 55 years or older who were admitted to a single level 1 trauma center with an operative hip fracture were included. Patient demographics, comorbidities, admitting service, complications, and hospital length of stay were recorded for each patient. Cost of hospitalization, discharge disposition, and 30-day readmissions were collected. Patients who were admitted to the medicine service (medicine cohort) were compared to those admitted to a surgery service (surgery cohort). Multivariate regression models controlling for age, Charlson comorbidity index (CCI), and American Society of Anesthesiology (ASA) scores were used to evaluate hospitalization costs with a P value of <.05 as significant. RESULTS: Two hundred twenty-five hip fracture patients were included; 143 (63.6%) patients were admitted to a surgical service, while 82 (36.4%) were admitted to the medicine service. Patients admitted to medicine service had greater CCI and ASA scores, longer lengths of stay, and more complications than those patients admitted to surgery service. Linear regression model controlling for age, CCI, ASA score, and time to surgery demonstrates that patients admitted to a surgical service will have 2.0-day (95% confidence interval [CI]: 0.561-3.503; P = .007) shorter admissions with a US$4215 reduction in cost (95% CI: US$314-US$8116; P = .034) compared to patients admitted to the medicine service. DISCUSSIONS: In our urban safety net hospital, hip fracture patients admitted to medicine service had longer lengths of stay and higher total hospitalization costs than patients who were admitted to surgery service. CONCLUSIONS: This study highlights that the admitting service should be an area of focus for hospitals when developing programs to provide effective and cost-conscious care to hip fracture patients.